Artificial Intelligence Literacy: A New Paradigm for Libraries - Demir, Güler (Information World, 2025)
When used consciously, critically, and with attention to ethical principles, the developing artificial intelligence (AI) technology tools provide effectiveness, speed, accuracy, and efficiency in meeting many needs of individuals, institutions, and organizations. It is essential to be artificial intelligence literate to recognize, understand, evaluate, and use artificial intelligence technologies effectively. This study aims to define artificial intelligence literacy, emphasize its importance, and examine the role of libraries in developing this literacy. In addition, it is to reveal the potential of artificial intelligence literacy to increase individuals’ ability to evaluate and use artificial intelligence technologies critically. Within the scope of the study, which was prepared with the qualitative description method and analyzed the relevant sources from domestic and foreign literature, the concept of artificial intelligence literacy was defined, the role of libraries in the development of this type of literacy was included, and the study was also supported with examples of the university and public libraries taken from the United States, Canada, Australia, and North America. The results obtained from the study’s findings indicate that the role of libraries in developing artificial intelligence literacy is crucial and that educational programs in this area should be strengthened. Libraries can guide the ethical and practical use of artificial intelligence technologies and enable individuals to benefit better from these tools. This research is considered to be original because there is no other study in the domestic literature that addresses the meaning of artificial intelligence literacy for libraries and evaluates the related foreign and domestic literature in a detailed and systematic way.
Keywords: AI literacy; ChatGPT; AI hallucination; prompt engineering; library; librarian